Effect of proton pump inhibitors on the risk of chronic kidney disease: A propensity score-based overlap weight analysis using the United Kingdom Biobank - Zhang, Xing-Yu; He, Qiang-Sheng; Jing, Zhong; He, Juan-Xia; Yuan, Jin-Qiu; Dai, Xiao-Yu (Frontiers in Pharmacology, 2022)
Background: Proton pump inhibitors (PPIs) are widely used and have been linked to kidney diseases. However, it remains unclear about the role of PPI use in the development of chronic kidney disease (CKD). We undertook this study to examine the association between PPI use and subsequent risk of CKD. Methods: This is a prospective analysis of 462,421 participants free of cancer diagnosis or chronic kidney disease from the UK Biobank. Self-reported PPI use was recorded using an electronic questionnaire, and confirmed by a trained staff. Incident CKD was identified based on medical history. Overlap propensity score weighting with Cox model was used to calculate the effect of PPI use on CKD risk. The number needed to harm (NNH) was calculated at five and 10 years of follow-up. Results: We documented 7,031 cases of CKD over a median of 8.1 years’ follow-up. Overlap propensity score weighting analysis showed that regular PPI users had a 37% higher risk of CKD incident compared to non-users (HR1.37, 95%CI 1.28 to 1.47). The association persisted across subgroup analyses, different types of PPIs and several sensitivity analyses. Quantitative bias analysis indicated that result was robust to unmeasured confounding (E-value 2.08, lower 95% CI 1.88). The NNH was 147.9 and 78.6 for five and 10 years of follow-up, respectively. A head-to-head comparison showed that PPI users had a 19% higher risk of CKD compared with H2RAs users (HR 1.19, 95% CI 1.02 to 1.39). Conclusions: Regular use of PPI is associated with a higher risk of CKD. Healthcare providers should carefully weigh up the potential benefits against risk in prescribing PPIs, particularly for patients requiring long-term treatment.